1984
DOI: 10.1227/00006123-198407000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan: A New Topical Hemostatic Agent for Diffuse Capillary Bleeding in Brain Tissue

Abstract: The effectiveness of chitosan as an intraoperative topical hemostatic agent for brain tissue was tested. Cerebral cortical lesions were made in 10 cats. Chitosan was used to obtain hemostasis. The elapsed time from the application of the hemostatic agent to hemostasis was determined. The animals were killed and the lesions were examined grossly and microscopically to evaluate the biocompatibility of chitosan. Chitosan was easy to apply and required minimal subsequent manipulation. Histopathological examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 0 publications
5
38
0
Order By: Relevance
“…It is considered as a suitable material for biomedical applications because of its nontoxic character, good biocompatibility, non-antigenicity, antitumor activity, and protein adsorption properties. It promotes cell adhesion and migration, enhances wound healing, and has tunable biodegradation rate by controlling its degree of deacetylation, molecular weight, and crystallinity [162][163][164]. Chitosan is tough and flexible, but lacks sufficient strength to be used alone in load-bearing applications.…”
Section: Bioceramic/polymer Composites For Bone Reconstructionmentioning
confidence: 99%
“…It is considered as a suitable material for biomedical applications because of its nontoxic character, good biocompatibility, non-antigenicity, antitumor activity, and protein adsorption properties. It promotes cell adhesion and migration, enhances wound healing, and has tunable biodegradation rate by controlling its degree of deacetylation, molecular weight, and crystallinity [162][163][164]. Chitosan is tough and flexible, but lacks sufficient strength to be used alone in load-bearing applications.…”
Section: Bioceramic/polymer Composites For Bone Reconstructionmentioning
confidence: 99%
“…The role of chitosan in aggregating the erythrocytes has been suggested by many authors. 2,4,6,[19][20][21] There could be a change in the surface charge of the chitosan and SAP as it interacts with the blood (pH 7.4) and the response would change with time. Interestingly though, the films have an observed effect upon the aggregation of blood cells.…”
Section: Blood Coagulation Testmentioning
confidence: 99%
“…A similar product, chitosan, was originally developed for use as a topical hemostatic agent (Malette et al, 1983;Brandenberg et al, 1984). Several studies have shown the effectiveness of chitosan alone or combined with other biomaterials for chemoembolization Nishioka et al, 1992;Wang et al, 1995;Denkbas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%